Audit Committee Expertise and Its Effect on Financial Disclosure Reliability (gjstudies, 2014)
This research investigates the nuanced relationship between the composition ofcorporate audit committees and the reliability of financial disclosures, proposing anovel framework that integrates computational linguistics, network analysis, and behavioral economics. While prior literature has examined audit committee characteristics broadly, this study introduces a multidimensional expertise index that capturesnot only traditional accounting and financial qualifications but also less-explored dimensions such as technological acumen, industry-specific experience, and cognitivediversity. The methodology employs a hybrid approach, combining archival financialdata from a sample of 350 publicly traded firms over a five-year period with computational text analysis of earnings call transcripts and annual reports. We develop aproprietary reliability scoring algorithm that assesses disclosure quality along dimensions of transparency, consistency, and predictive accuracy. Our findings reveal thataudit committees with higher technological expertise scores are associated with a 23%improvement in the reliability of forward-looking disclosures, particularly in sectorsundergoing digital transformation. Furthermore, we identify a non-linear relationshipbetween financial expertise concentration and disclosure reliability, where committeeswith moderate diversity in expertise backgrounds outperform both homogeneous andhighly heterogeneous groups. The study also uncovers a previously undocumented’oversight paradox,’ wherein committees with excessive accounting expertise may inadvertently reduce disclosure reliability through over-auditing behaviors that suppressmanagerial communication. These results contribute to corporate governance theory bychallenging the conventional wisdom that more financial expertise uniformly enhancesoversight quality, and offer practical implications for board composition and regulatorystandards. The research demonstrates that a more holistic, computationally-informedassessment of audit committee capabilities can significantly improve our understandingof financial reporting ecosystems